Development of dispersive solid phase extraction method for the preconcentration of parathion ethyl as a simulant of nerve agent sarin from soil, plant and water samples prior to GC-MS determination - Bodur, Sueleyman; Bodur, Sezin Erarpat; Tutar, Bahar Karademir; Bakirdere, Sezgin; Yagmuroglu, Ozan (SPRINGER, 2024)
In the presented study, an efficient and fast analytical method was developed for the determination of parathion ethyl as sarin simulant by gas chromatography-mass spectrometry (GC-MS). Dispersive solid phase extraction (DSPE) was performed to concentrate parathion ethyl from soil, plant and water samples. Reduced graphene oxide-iron (II, III) oxide (rGO-Fe3O4) nanocomposite was used as an adsorbent to collect the target analyte from the aqueous sample solutions. After the optimization of extraction/preconcentration parameters, optimum conditions for adsorbent amount, eluent type, mixing type/period, eluent volume and initial sample volume were determined as 15 mg, acetonitrile, vortex/30 s, 100 mu L and 10 mL, respectively. Under the optimum conditions, analytical performance of the developed DSPE-GC-MS method was evaluated in terms of limit of detection (LOD), limit of quantitation (LOQ) and dynamic range. Dynamic range, LOD and LOQ values were figured out to be 0.94-235.15 mu g/kg, 0.41 mu g/kg and 1.36 mu g/kg (mass based), respectively. Satisfactory percent recovery results (90.3-125% for soil, 93.5-108.7% for plant, 88.5-112.9% for tap water) were achieved for soil, plant and tap water samples which proved the accuracy and applicability of the developed method. It is predicted that the DSPE-GC-MS method can be accurately used for the detection of sarin in soil, plant and water samples taken from war territories.
Keywords: Dispersive solid phase extraction; Sarin gas; Parathion ethyl; Chemical weapon; WALLED CARBON NANOTUBES; ENVIRONMENTAL-SAMPLES; OXIDE NANOCOMPOSITES; GAS-CHROMATOGRAPHY; HUMAN SERUM; GRAPHENE; SPECTROMETRY; SEPARATION; Environmental Sciences & Ecology